Enhanced SVD watermarking algorithms - Tehrani, Iman Omidvar (2011)
inbox unpub unspecified FSKSM 2011-00 completed 75 Universiti Teknologi Malaysia, Faculty of Computer Science and Information System Faculty of Computer Science and Information System masters thesis